C-reactive protein: pathogenetic characteristics and possible therapeutic target - E. A. Utkina; O. I. Afanasyeva; S. N. Pokrovsky (Российский кардиологический журнал)
It is known that the key mediator of acute phase response and marker of inflammation is C-reactive protein (CRP), the study of the role of which in the development of not only cardiovascular, but also infectious diseases has acquired particular relevance at the present time. CRP can be involved in all stages of the atherosclerotic process, including activation of the complement system and vascular endothelial cells, thrombosis, lipid accumulation, and apoptosis.The review describes modern concepts of the structure, biological and pathophysiological properties of CRP, its value as a cardiovascular risk predictor, as well as existing methods for reducing its blood level.According to recent studies, cardiovascular patients who achieved lower CRP levels with drug therapy had better clinical prognosis, making CRP an attractive therapeutic target. Currently, a search is underway for approaches to correct CRP levels associated with both the development of novel drugs and therapeutic apheresis methods to remove CRP from blood plasma.